(3efgL GdSGdc Edi CdajI GHf eGdcs - (3CHhGdMSf fhQGdOjf Ydj Hf eMeO Hf YjSi GdCTehfjs; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi eG efM ef CSHGH GdHjGf agPG TQM dWja HOjY Ydi CdajI GHf eGdc s
(3BNQgG (B:s
(3hGdNUGUI VO GdZfi, hgh cfGjI YeG LeY ef GdeMGSf GdXGgQI Ke bGHd HGdTcQ fYeI GdEJeGe s
(3ThGgO GdTYQ eVHhWI HGdTcds
(3HgG fXGe GdJYbjHIs
(3cJHJ YHGQGJ GdCUds
(3GdYHGQGJ GdegeI HGdMeQI s
(3aj GdeYgO fSNI CNQi GfXQgG aj GdLRA GdChd (B172 (3fMh s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs